2019
DOI: 10.1042/bsr20182224
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA TCONS_00000200 as a non-invasive biomarker in patients with intracranial aneurysm

Abstract: We performed long non-coding RNA (lncRNA) microarray assay to identify lncRNAs with differential expression between patients with intracranial aneurysm (IA) and healthy control individuals to evaluate their potential use as biomarkers of IA. Arraystar Human lncRNA Microarray v3.0 was performed to identify differentially expressed lncRNAs and mRNAs in plasma samples (4 ml). lncRNAs with the most pronounced differential expression were used to select gene markers, and results were validated by quantitative rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In expression studies in blood samples, RNAs were isolated from whole blood [ 33 , 34 , 35 , 36 , 37 ], blood cells as a whole [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], or specifically from leukocytes [ 24 ], mononuclear cells [ 45 , 46 , 47 ], or neutrophils [ 48 , 49 , 50 ]. Circulating RNAs were isolated from plasma [ 51 , 52 , 53 , 54 , 55 ], serum [ 56 ], or circulating exosomes [ 57 ]. The main goals of this group of studies were: (i) search of biomarkers of IAs or their categories (RAs, UAs), and (ii) investigation of systemic consequences of IA rupture, including clinical status of SAH patients or SAH complications such as vasospasm [ 33 , 44 ] or DCI [ 38 ].…”
Section: Original Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In expression studies in blood samples, RNAs were isolated from whole blood [ 33 , 34 , 35 , 36 , 37 ], blood cells as a whole [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], or specifically from leukocytes [ 24 ], mononuclear cells [ 45 , 46 , 47 ], or neutrophils [ 48 , 49 , 50 ]. Circulating RNAs were isolated from plasma [ 51 , 52 , 53 , 54 , 55 ], serum [ 56 ], or circulating exosomes [ 57 ]. The main goals of this group of studies were: (i) search of biomarkers of IAs or their categories (RAs, UAs), and (ii) investigation of systemic consequences of IA rupture, including clinical status of SAH patients or SAH complications such as vasospasm [ 33 , 44 ] or DCI [ 38 ].…”
Section: Original Studiesmentioning
confidence: 99%
“…Korostynski et al [ 41 , 42 ] and Morga et al [ 43 ] analyzed differences in RNA expression profiles between acute and chronic phase of RA, whereas van’t Hof et al searched for potential biomarkers of past aSAH (at least 2 years after RA) [ 40 ]. Similar to tissue-based studies, in most of the blood-based studies, mRNA expression was examined (cell-derived or circulating) [ 24 , 34 , 37 , 38 , 39 , 40 , 41 , 44 , 45 , 47 , 48 , 49 , 50 , 53 ]. However, non-coding RNAs were also studied—mainly miRNAs [ 33 , 42 , 51 , 52 , 54 , 55 , 56 , 57 ] and lncRNAs [ 24 , 35 , 53 ].…”
Section: Original Studiesmentioning
confidence: 99%
“…Interesting, the expression level of circulating MEG3 was increased with the elevation of Hunt-Hess grade, which achieved the peak in SAH patients with Hunt-Hess IV-V, indicating that circulating MEG3 can be served as an indicator of SAH severity. Additionally, in another experiment of IAs, microarray assays showed that 797 circulating lncRNAs in the plasma were differentially expressed (519 upregulated and 278 downregulated) [60]. Of these, 10 circulating lncRNAs with the largest differential expression were selected for qRT-PCR validation.…”
Section: Lncrnas As Non-invasive Biomarkersmentioning
confidence: 99%
“…With the accumulation of studies about immunization, non-coding RNAs and epigenetics, the molecular mechanisms of IA have been widely identified. However, although numerous studies have explored microRNAs (miRNAs) (3)(4)(5) or long non-coding RNAs (lncRNAs) (6,7) in IA, circRNAs in IA, particularly in MIA, have remained largely elusive. The genetic pathology of MIA, particularly in terms of circular RNAs (circRNAs) in MIA, remains to be determined.…”
Section: Introductionmentioning
confidence: 99%